SIMULATION MODEL FOR PREDICTION OF STAND GROWTH AND YIELD OF Tectona grandis Linn F. IN AKINYELE LOCAL GOVERNMENT AREA, OYO STATE, NIGERIA (2014)
Effective management planning tools for forest require growth and yield functions that can produce detailed predictions of stand development. Models such as Gamma Distribution Function (GDF), Weibull, Beta, and similar functions have been used to predict growth and yield of forest stands. However, information on the use of GDF in forest management has not been fully documented. The development of a program using Java programming language for GDF to predict growth and yield of Tectona grandis was studied in Akinyele Local Government Area, Oyo State, Nigeria. Stratified random sampling was used to select four different age classes of teak plantation namely; 11, 13, 22 and 59 years. Based on the size of each plantation, 7 and 8 temporary sample plots of 0.04 ha were selected from 11, 13, 22 and 59 year-old plantations respectively. Complete enumerations of trees (n = 433.) was done. Growth data sets collected include Diameter at Breast Height (DBH), total and merchantable heights. Basal Area (BA) and Volume were computed from measured variables. Data obtained were processed into tree level, stand level and size class. Parameters α and β for GDF were estimated from growth data. Based on the algorithm of GDF, α, β and n parameters, for the Java Program (JP) was written. Values obtained were fitted into the JP for growth and yield prediction. Linear and non- linear models were used to compare their predictive ability to the JP developed. At individual tree level using JP, the Observed and Predicted (O&P) values for height and BA ranged from 16.80-43.80 m, and 16.10-39.30 m; 2.49-4.51m2, and 2.45-4.31m2. Volume ranged from 2.09-10.54m3 and 2.04-12.03m3. Error rate varied from 0.00-9.00, -23.09-4.99 and -14.09-5.27 for height, BA and volume respectively. At stand level the O&P values for height, BA and volume from JP ranged from 17.10-28.30 and 17.90- 32.10 m; 2.55-3.69 m2 and 2.58-3.69m2; 2.25-3.69m3 and 2.28-3.69 m3 with error rate of -2.77-13.4; -0.10-5.65 and -0.10 -0.40 respectively. Size class level shape and scale parameter of GDF for diameter distribution ranged from 0.96-25.20 and 0.07-2.28 respectively. These values have better predictive power than non-linear and linear models which at individual tree level, O&P values for height and BA models of best fit ranged from 16.80-43.80m and 15.86-39.00 m; 2.49-4.51m2 and 2.50-4.98m2 . For volume, it ranged from 2.09-10.54m3 and 2.02-12.05m3 with error rate of -14.32-6.37. At stand level, O&P ranged from 17.10-28.30m and 17.95-32.18m for height; 2.55-3.69 and 2.59-3.72 m2 for BA and 2.25-3.69 and 2.29-3.65m3 for volume with error rate from -2.88-13.71; -4.58 -0.81 and -1.77-1.08 respectively. The R2 values for height, BA and volume models of best fit were 0.9490, 0.8981 and 0.9800 with the equations given as H= [1.31.08 + (H1.08 dom -1.31.08)1-e-0.06dbh/1-e-0.06*1.08 dom]1/1.08, 1n(B) = ln(0.32)+ 0.42(1/A)+ 0.77(lnH)+1.82(lnN)+1.89(H/A) and V= 1.62+22.38*DBH. The predictive ability of gamma distribution function for height, basal area and volume for teak plantation from the developed Java program consistently performed better than other models and could therefore be used for prediction of growth and yield in forest stands. Keywords: Gamma distribution function, Teak plantation, Growth and yield models, Forest management Word count: 498